System celów jako przedmiot wyboru strategicznego - Stabryła, Adam (System of objectives in strategic choice, 2006)
The objective of this paper is to present a concept of designing systems of objectives. The major problems discussed in the paper are as follows: Formulas of objectives; Classifying factors of objectives; Principles of designing system of objectives; Techniques of selecting objectives; Strategic option as variants of selecting objectives; Methodology of the analysis of strategic options.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 157-167